The Dynamic Impact of Corporate Governance on Investment Decisions of Non-Financial Companies in Sri Lanka - Nazar, MCA. , (The journal of contemporary issues in business and government, 2021)
This research examines the influence of corporate governance on investment decision of 198 non-financial companies listed on the Colombo Stock Exchange of Sri Lanka, over the period from 2009 to 2016. This study used four corporate governance variables such as managerial ownership, board size, board independence, and CEO duality. Moreover, this study considers three control variables such as profitability, firm size, and corporate tax. This study employed the Generalized Method of Moments (GMM) model to estimate the regression models on panel data study. The main contribution of this study is sightseeing the insight of the effect of corporate governance factors on investment decisions. Findings reveal that managerial ownership is positively significantly influence on investment decision. Board size is insignificantly positive on investment decision. The existence of positive effect between board independence and changes in total assets was found in the study and a significant negative influence on Tobin’s Q.CEO duality is significantly and negatively related to changes in total assets and it is significantly and positively connected to Tobin’s Q. Therefore, except for board size, all the other corporate governance factors have influence on the investment decision of a firm.